Peristeria oscarii‐rodrigoi sp. nov. – first record of the genus Peristeria (Orchidaceae) from Guatemala. (10th June 2015) - Archila, Fredy; Szlachetko, Dariusz L.; Kolanowska, Marta; Narajczyk, Magdalena; Dudek, Magdalena
<x xml:space="preserve">Abstract</x> A new species of the orchid genus Peristeria is described and illustrated and information about its habitat and ecology is provided. So far the new species is known exclusively from the municipality of Senahú in the Guatemalan Department of Alta Verapaz. The species is the first representative of Peristeria found in Guatemala. The finding described here expands the geographical range of the genus to the northern part of Central America.